ANALISIS MANAJEMEN PESERTA DIDIK DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR NEGERI BANJARSARI 4 KOTA SERANG - Syachruroji, A.; Rokmanah, Siti; Hakim, M. Rizky Al (LPPM Universitas Bina Bangsa, 2024)
This study aims to analyze the improvement of school quality through student management at Elementary School Banjarsari 4. Descriptive qualitative method is the research method used in this study. The data collection techniques used in this study were observation, interviews, and documentation. So the results of this study show that all schools implement student management starting with planning, organizing, fostering and developing, evaluating and organizing graduates. This application will have an impact on improving the quality of schools in academic and nonacademic aspects